Localising vibrating scatterer phenomena in synthetic aperture radar imagery - Corbett, Brandon; Andre, Daniel; Finnis, Mark V. (Institution of Engineering and Technology (IET), 2020)
Artefact phenomena resulting from synthetic aperture radar (SAR) image formation can pose a challenge for image interpretation. One such artefact is produced when a vibrating target is imaged. Suppression of these artefacts has previously been described, however little has been developed in the area of modelling the location and shape of such artefacts. The authors present an experimentally validated model that provides accurate location and shape of vibrating target paired echoes in both SAR near-field and SAR far-field imagery.
Keywords: Synthetic aperture radar; Vibrating target phenomenology; Micro-Doppler analysis